AKTIVITAS SEDIAAN SALEP EKSTRAK BATANG POHON PISANG AMBON (Musa paradisiaca var sapientum) DALAM PROSES PERSEMBUHAN LUKA PADA MENCIT (Mus musculus albinus) - Bayu Febram; Ietje Wientarsih; Bambang Pontjo (Faculty of Pharmacy, Universitas Gadjah Mada, 2010)
The objective of the present research is to study the activity of banana stem extract in ointment solutions in the acceleration of wound healing process on mice skins. Totally of 45 mice strain DDY 4-6 weeks old were devided in negativecontrol group (placebo ointment), positive control group (Betadine® ointment) and Ambon banana stem extract ointment.All mice were aseptically wounded 1-1,5 cm in the anterior region of back skin using a sterile scalpel. The wound wassmeared with the ointment. The pathology anatomy observations was done inday 3, 5, 7, 14 and 21 post wounded. Parameters of the gross lesions (pathology anatomy) observations warecolour of the wound, blood coagulations, scab formations and size of the wound. Parameter for (microscopic lesions) histopathology were infiltrations of inflammatory cells (neutrophils, lymphocytes,macrofages), neo-capillarizations, re-epitelization percentage and the thickness of fibroblast. All quantitative data were measure using ANOVA and continue with Duncan Test, moreover, the qualitative data were presented descriptively. The result shows that gross lesions observations, the extract ointment group was faster in scab formations and covers the wound without trace compared to the negative control group. The statistical test on the infiltrations of inflammatory cells parameter of the extract ointment group significantly different (P<0.05) compared to the negative control group. Histopatologycal observations shows that Ambon banana stem extract in ointment solutions can increase the infiltrations of inflammatory cells, neo-capillary formations, re-epitelizations percentage andacceleration of fibroblast formations. Base on the result the Ambon banana stems extract in ointment solutions can accelerate the wound healing process and it seems that this solution could be developed and uses for the medical purposes.